Afrofuturo: um tarô afrofuturista brasileiro - Almeida, Amanda Mendes de (2020)
Futuristic science fiction narratives have always had white people as protagonists. This is another indication of how racism moves us, to the point that the project, whose main objective is to exterminate the black population, is transparent in the popular imaginary, which idealizes the future without black people in it. It is for this reason that the Afrofuturist movement appears, as a response to the post-diasporic blackness that, when investigating the past that kidnapped, erased and violated them, re-signifies it in the present, provoking new imaginary that configure a vision of the future filled of technology, mysticism, and cultural elements of the motherland: Africa. Beyond the ideals of that future, this project consists in the major arcanas of a Brazilian Afrofuturism tarot, a tool for the maintenance and propagation of black brazilian memory, in addition to promote the reconstruction of their identity in the collective unconscious. If the problem is in the popular imaginary, only the Tarot cards with its archetypes can make us reflect on the unconscious “self”, consequently helping us to work with the issues that we have already observed in the conscious, promoting changes, resisting, and so, combating structural racism. With this, the present project was accomplished through the use of public archive images on the internet, together with photographs taken at a distance, gathered aesthetically using the collage technique, and digital retouching at its completion